Penambahan ekstrak tepung albedo semangka merah (Citrullus vulgaris Schard.) sebagai penstabil pada es krim susu kambing - Bernadetta Hera Darmaningtyas; Franciscus Sinung Pranata; Yuliana Reni Swasti (AGROINTEK, 2024)
Ice cream is a semi-solid food that is loved by all people. Goat's milk can be used in making ice cream because some of the nutritional content of goat's milk is superior to cow's milk, one of which is in terms of the composition of high medium chain fatty acids and fat globules with smaller diameters that are easily digested and beneficial for health. Red watermelon albedo flour extract (Citrullus vulgaris Schard.) contains pectin which can be used as a stabilizer. This study aims to determine the effect of adding variations in the concentration of red watermelon albedo flour extract on the quality of goat's milk ice cream in terms of chemical, physical, microbiological and organoleptic aspects and to determine the optimum concentration of using red watermelon albedo flour extract as a stabilizer. The experimental design used in this study used a completely randomized design (CRD) with 4 treatment concentrations of addition of red watermelon albedo flour extract, namely a concentration of 0% (control with CMC); 0.1%; 0.3% and 0.5%. The results showed that the addition of red watermelon albedo flour extract did not have a significant effect on the melting rate, fat content, total solids, sucrose content of total plate number (ALT) and Salmonella but had a significant effect on the overrun and protein content of goat's milk ice cream resulting from. The addition of 0.5% red watermelon albedo flour extract resulted in goat's milk ice cream with a melting rate of 18.72%; overrun of 29.11%; fat content of 6.32%; protein content of 4.49%; total solids by 39.95%; sucrose content of 41.75%; the total plate number is 2.71 x 102 CFU/g; negative Salmonella and the organoleptic value was 3.43.